ANALISIS FAKTOR PENYEBAB TINDAKAN TIDAK AMAN BAGIAN WORK OVER SERVICES SAAT MENCABUT PLUNGGER PUMP DI OPERASIONAL RIG 06 PT. GENERAL BUDITEKINDO KM.06 DURI-RIAU - Friska Eka Fitria; Dina Waldani (Ensiklopedia of Journal, 2022)
A near miss case occurred in a Work Over Services worker when removing the Plunger Pump at Operational Rig 06 PT. General Buditekindo Km. 06 Duri-Riau, there were 20 cases throughout 2020 caused by workers taking unsafe actions. The purpose of this study was to analyze the factors causing Unsafe Action in the Work Over Services section when removing the plunger pump at Rig 06 operation PT. General Buditekindo Km. 06 Duri-Riau. This type of research is descriptive qualitative. The research was conducted from April to August 2022. The informants of this research are the main informants (1 person Driller, 1 person Drigmen, 2 people Floorman, 1 person Roustabout), key informants (1 person Hse), supporting informants (1 person manager, HRD 1 person). The factors analyzed were predisposing factors (motivation), supporting factors (availability of PPE), reinforcing factors (supervision. The results based on motivation factor analysis showed that the motivation of workers when removing the plunger pump was still low, based on the availability factor of PPE, it was found that PPE had been provided. complete by the company, but in practice the use of the workers still does not use complete PPE, based on the monitoring factor, the results show that supervision is carried out every day by ToolPusher and the HSE department through online and offline CCTV in the field. For future improvements, the company is expected to make a commitment to the implementation principles of occupational safety and health (K3) through the provision of punishments and rewards to workers through safety awards, giving strict sanctions to workers who do not use PPE and giving direct warnings to workers who act unsafely.